Coinfection of some respiratory viruses in cattle: An abattoir study - Intisar K. Saeed; Yahia H. Ali; Muaz Magzoub Abdellatif; Alaa Mustafa; Ahmad M. Abdel-Mageed (Onderstepoort Journal of Veterinary Research)
To investigate the existence of bovine viral diarrhoea virus (BVDV), parainfluenza virus 3 (PIV-3) and respiratory syncytial virus (RSV) as well as its coinfections, a total of 420 pneumonic lung tissue samples were collected from slaughterhouses in three different areas. Samples were examined for the three viruses using antigen detection enzyme-linked immunosorbent assay (ELISA) test, and positive results were further confirmed using fluorescent antibody test and polymerase chain reaction. Prevalences detected were 10.47% for BVDV, 11.9% for parainfluenza virus type (PIV-3) and 7.6% for respiratory syncytial virus (RSV). Observed coinfections were bovine viral diarrhoea (BVD) and PIV-3 in 8.1%, BVD and RSV in only two samples (1%). Existence of all three viruses was detected in two samples (1%).